Negative electrode slurry, lithium ion battery and preparation method thereof

By using carbon nanotube conductive agent and modified styrene-butadiene rubber in the negative electrode slurry of lithium-ion batteries, combined with graphite inlay structure and high-temperature pre-carbonization technology, the lithium-ion battery's high-speed discharge and long cycle life is solved. Inadequately, efficient fast charging and long-life performance are achieved.

CN119252915APending Publication Date: 2025-01-03HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411370807.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in high-rate discharge and long cycle life, especially in the field of energy storage, which is difficult to meet high requirements.

Method used

The composition of the negative electrode slurry is 90~94.8% of the negative electrode active material, 1.9~2.2% of the negative electrode conductive agent, 0.01~0.05% of the super conductive agent, 1.2~1.4% of the carboxymethylcellulose and 2% of the negative electrode bonding. The super conductive agent is a carbon nanotube conductive paste, and the negative electrode binder is acrylic modified styrene butadiene rubber. The graphite raw material inlay structure and composite granulation technology are combined with high-temperature pre-carbonization technology to improve the magnification and circulation performance.

Benefits of technology

The fast charging performance of lithium-ion batteries in continuous charging at 3C-4C and continuous discharge of 6.5C-9.5C is achieved. The maximum temperature does not exceed 55℃, the discharge cut-off voltage is > 2.7V, and the cycle life reaches 1C/1C 5000 weeks, which is significantly improved. Comprehensive performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses negative electrode slurry, a lithium ion battery and a preparation method of the lithium ion battery. The negative electrode slurry comprises the following components in parts by mass: 90-94.8 parts of a negative electrode active material; 1.9 to 2.2 parts of a negative electrode conductive agent; 0.01 to 0.05 part of a super conductive agent; 1.2 to 1.4 parts of carboxymethyl cellulose; 2 parts of a negative electrode binder; wherein the super conductive agent is carbon nano tube conductive slurry. The lithium ion battery comprises a positive plate, a negative plate, a diaphragm, electrolyte, a shell related structural member and a connecting plate, and the negative plate comprises a negative current collector and negative slurry coated on the negative current collector. According to the lithium ion battery, high-rate discharge is met, and meanwhile good cycle performance is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a negative electrode slurry, a lithium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have an increasingly profound impact on modern life. They are currently used in new energy vehicles and energy storage power stations, especially large energy storage power stations. As a reserve power source, especially for portable energy storage and household energy storage, they need to continuously meet high-rate discharge and long cycle life during operation. Therefore, high-rate lithium-ion discharge has become a major problem that needs to be solved in the field of lithium-ion battery energy storage to catch up with the needs of the times. Currently, the publication number CN 111799500 A is a lithium cobalt oxide battery, and it is a soft-pack battery that can meet 25C discharge, but does not specify the maximum temperature and cut-off voltage, and does not reflect the cycle life problem; the publication number CN 105552428 A mainly improves the discharge rate from the structural aspect, but does not specify its cycle life, discharge time and temperature rise, and it is a lithium cobalt oxide system; therefore, it is urgently needed to bring a lithium ion battery that can meet the high-rate discharge of lithium phosphate and long cycle life to the market to develop the energy storage market. Summary of the invention

[0003] The purpose of the present invention is to provide a negative electrode slurry, a lithium ion battery and a preparation method thereof. The lithium ion battery of the present invention satisfies high rate discharge and ensures good cycle performance.

[0004] The present invention provides a negative electrode slurry, which comprises the following components in parts by weight: Negative electrode active material 90~94.8 parts; 1.9~2.2 parts of negative electrode conductive agent; Super conductive agent 0.01~0.05 parts; 1.2-1.4 parts of carboxymethyl cellulose; 2 parts of negative electrode binder; Wherein, the super conductive agent is carbon nanotube conductive slurry.

[0005] In the present invention, the carbon nanotube conductive slurry is a composite of single-wall and multi-wall, the carbon tube itself is of high quality, and the carbon tube dispersant used has less effect on the conductivity of the carbon tube itself and better dispersibility, so the overall material utilization rate is greatly improved, and more three-dimensional parallel networks can be constructed in the electrode, with better conductivity; specifically, it can be a commercially available product, model LB126B-23, oil-based, with an effective solid content of 2.4%.

[0006] In the above-mentioned negative electrode slurry, the negative electrode binder is styrene-butadiene rubber modified by acrylic acid, which can be purchased from Daoying Technology Co., Ltd. with a product catalog number of GD1331.

[0007] In the above-mentioned negative electrode slurry, the negative electrode active material is graphite; The graphite raw material has an inlay structure ratio of 20-40%. The graphite has a secondary particle structure, and its aggregate particle size D50 can be 6-8 μm, and the secondary particle D50 can be 11 μm-14 μm.

[0008] In the present invention, the graphite raw material used has a mosaic structure ratio about twice as high as that of ordinary petroleum coke, and has good isotropy; at the same time, the aggregate particle size D50 of the graphite is controlled at ~8μm, and the small-diameter graphite particles shorten the lithium ion deintercalation distance and have better rate performance; the secondary particle structure and the high-complexity secondary particle structure improve the isotropy of the particles, and secondly, the process adopts advanced pretreatment technology to improve the energy density and high-temperature performance; the composite granulation technology improves the isotropy of the particles and improves the rate and cycle performance; the low-temperature pre-carbonization and high-temperature graphitization technology control the graphitization layer spacing, which is beneficial to the lithium ion deintercalation, improves the rate performance and ensures a certain energy density.

[0009] In the above-mentioned negative electrode slurry, the average tube diameter of the super conductive agent can be 1.56~1.8 nanometers, specifically 1.76 nanometers, the slurry aspect ratio can be 1340~2340, and the resistance conductivity is 0.28~0.34 Ocm, specifically 0.3065Ocm.

[0010] The present invention also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, and shell-related structural parts and a connecting sheet. The negative electrode sheet comprises a negative electrode collector and the negative electrode slurry coated on the negative electrode collector.

[0011] In the above-mentioned lithium-ion battery, the positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on the surface of the positive electrode current collector; The positive electrode slurry comprises the following components in parts by weight: 90-95.5 parts of positive electrode active material; 1.3-1.8 parts of positive electrode conductive agent; 1.8-2.2 parts of positive electrode conductive slurry; and 2.0 parts of positive electrode binder.

[0012] In the above-mentioned lithium-ion battery, the positive electrode active material is lithium iron phosphate LFP, the gram capacity is ≧145 mAh / g, and the median particle size D of the positive electrode active material is 50 It can be 0.6~1.5um, and the ultimate compaction density can be 2.25~2.3g / cm 3 ; The positive electrode conductive agent is a mixture of graphene and conductive carbon black (SP), and a conductive network composed of points and surfaces is selected to improve the conductivity of the positive electrode iron lithium pole piece; The positive electrode binder is polyvinylidene fluoride (PVDF), and the main chain of PVDF is -(CH2-CF2)n -chain segment, and at the same time, molecules containing -COOH functional groups are embedded in the main chain segment to enhance the adhesion between PVDF and the positive electrode current collector and improve the battery cycle performance.

[0013] In the present invention, the positive electrode conductive paste may specifically be a graphene sheet conductive paste; The positive electrode slurry comprises the following components in parts by weight: 94.5 parts of positive electrode active material; 1.5 parts of positive electrode conductive agent; 2.0 parts of positive electrode conductive slurry; and 2.0 parts of positive electrode binder.

[0014] In the above-mentioned lithium-ion battery, the diaphragm is a PE ceramic diaphragm or a PP base film, and at the same time, the PE ceramic diaphragm is coated with PMMA large particle glue; The conductivity of the electrolyte can be 10~12 mS / cm. The electrolyte is prepared by dissolving a lithium salt in an organic solvent and adding an additive; wherein the organic solvent is a mixed solvent composed of EC, PC, and EMC; the lithium salt is at least one of LiClO4, LiPF6, LiAsF6, LiBF4, Li(CF3SO3) and Li(CF3SO2)2N, and the lithium salt is preferably LiPF6; the additive is one of sulfur-containing organic matter, fluorinated organic matter, vinylidene-containing organic matter, nitriles, boric acid, and silicate, and the additive is preferably VC, and 20% DMC is added to improve wetting, increase rate and cycle performance.

[0015] In the above-mentioned lithium-ion battery, the single-sided surface density of the positive electrode sheet may be 125-150 g / m, and the average compaction density may be 2.13-2.18; The surface density of the negative electrode sheet may be 60-70 g / m, and the average compaction density may be 1.35-1.45.

[0016] The present invention further provides a method for preparing the lithium ion battery, comprising the following steps: S1. Prepare positive electrode slurry by mixing the raw materials of positive electrode slurry according to the main screw slurry method; S2, preparing negative electrode slurry by mixing raw materials of negative electrode slurry according to the main screw slurry method; S3, coating the positive electrode slurry and the negative electrode slurry on the positive electrode collector and the negative electrode collector respectively, and baking to obtain the positive electrode sheet and the negative electrode sheet; S4, rolling, slitting, winding, assembling, shelling, baking, liquid injection, sealing, infiltration, formation, aging, and capacity separation are performed on the positive electrode sheet and the negative electrode sheet respectively to obtain the lithium ion battery.

[0017] The present invention has the following beneficial effects: The lithium ion battery provided by the present invention has a structural size of a battery cell of 42100140-50AH, which ensures the capacity of the battery cell while ensuring fast charging and discharging performance and cycle performance. The battery cell can support 3C-4C continuous charging, and has a fast charging performance of 20% compared with lithium ion batteries currently on the market, and can meet 6.5C and 9.5C continuous discharge for 5 minutes, the maximum temperature does not exceed 55°C, and the discharge cut-off voltage is greater than 2.7V, which is 100% higher than the battery cells shipped on the market. The lithium ion battery provided by the present invention has good cycle and rate performance as well as high and low temperature discharge performance, has better comprehensive performance, and has a broad application market, especially in the field of energy storage. The cycle life meets 1C / 1C5000 weeks at room temperature and 1C / 1C 3000 weeks at high temperature, which is beneficial to the use of energy storage station backup power, and the negative electrode binder is styrene-butadiene rubber SBR modified by acrylic acid, which can improve the bonding performance with the graphite surface, while reducing the floating of SBR, increasing the dispersibility of the slurry and improving the cycle performance of the negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Flow chart of the preparation of positive electrode slurry in Example and Control Group 1.

[0019] Figure 2 Flow chart of the preparation of negative electrode slurry in Example and Control Group 1.

[0020] Figure 3 A 6.5C discharge curve comparison and a temperature rise curve comparison of square aluminum shell batteries were prepared for the example and the control group; Figure 3 (A) is the comparison of 6.5C discharge curves, and (B) is the comparison of temperature rise curves.

[0021] Figure 4 The square aluminum shell battery and the 9.5C discharge curve comparison and the temperature rise curve comparison were prepared for the embodiment and the control group; Figure 4 (A) is the comparison of 9.5C discharge curves, and (B) is the comparison of temperature rise curves.

[0022] Figure 5 The cycle curves of the batteries prepared in Example 1 and Control Group 1 at room temperature (25°C) at the same rate.

[0023] Figure 6 High temperature (45°C) cycle curves of the batteries prepared in Example and Control Group 1 at the same rate.

[0024] Figure 7 The cycle curves of the batteries prepared in Example and Control Group 1 at 1C / 6.5C at room temperature (25°C). DETAILED DESCRIPTION

[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0026] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0027] The present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The full names of the abbreviations or abbreviations of the substances in this embodiment are as follows: LFP is lithium iron phosphate, GO is graphene sheet conductive paste, SP is conductive carbon black, EC is ethylene carbonate, PC is propylene carbonate, EMC is ethyl methyl carbonate, VC is vinylene carbonate, and PVDF is polyvinylidene fluoride; The acrylic acid-modified styrene-butadiene rubber SBR used in the examples is a commercial product (purchased from Daoying Technology Co., Ltd., product catalog number GD1331); The super conductive agent is a carbon nanotube conductive slurry which is a commercially available product, model LB126B-23, oil-based, with an effective solid content of 2.4%.

[0029] Example (1) Preparation of positive electrode slurry: Figure 1 The process shown in the figure was prepared. The materials LFP:SP:GO:PVDF=94.5:1.5:2.0:2.0 were weighed according to the following mass percentages. NMP (N-methylpyrrolidone) 1 was put into the feeding mixer. According to the flow meter, spiral mixing was performed. The main screw speed was (550±10) rpm and slowly stirred for half an hour. The main screw solid content was (70±2). The main screw discharge viscosity was 6000~10000 mPa·s. Then, a high-speed disperser was used to crush large particles. Then, a high-speed disperser was used and stirred at high speed for 4 hours. The rotation and rotation were as follows. Figure 1 As shown in , the viscosity and solid content of the slurry were measured, the solid content was controlled at 64%, and the viscosity range was 3000-8000 mPa·s. During the whole process, the moisture content in the workshop was strictly controlled to be less than 25% to obtain the positive electrode slurry; (2) Preparation of negative electrode slurry: Figure 2 The process shown is prepared by mixing the ingredients according to the following mass percentages: Graphite 94.7%, carboxymethyl cellulose 1.3%, conductive carbon black SP 1.98%, super conductive agent 0.02%, acrylic acid modified styrene butadiene rubber 2%, then spiral mixing, scraping, main screw speed (550 ± 10) rpm slow stirring for half an hour, main screw solid content (70 ± 2), main screw discharge viscosity 6000 ~ 10000 mPa s and solid content (52 ± 3)%. Then high-speed dispersion, speed (4200 ± 200) rpm, measure slurry viscosity and solid content, solid content controlled at 64%, viscosity range of 3000 ~ 8000 mPa s.

[0030] (3) Pole sheet production: The prepared positive electrode slurry and negative electrode slurry are coated on the positive electrode collective fluid and the negative electrode collector respectively. The surface densities of the positive and negative electrodes are: single side: (125±2) g / m 2 , double-sided: (250±3) g / m 2 , single side: (60±2) g / m 2 , double-sided: (120±3) g / m 2 Rolling, positive electrode rolling thickness (132±2)μm, negative electrode first rolling: (107±2)μm, second rolling: (97±2)μm. The positive and negative electrode slitting width is 124 / 128mm; (4) Coiling, hot pressing, pre-welding, ultrasonic welding, core laminating and gluing; (5) Battery assembly: ultrasonic welding, core encapsulation, hot stamping and film encapsulation, laser welding, shelling, baking, primary liquid injection, high temperature immersion for 20 hours, formation, secondary liquid injection, and capacity separation to produce iron-lithium square lithium-ion batteries.

[0031] The baking parameters are as follows: preheating and drying: Step 1: vacuum (50-100) Pa; Step 2: nitrogen drying 98kPa Step 3: preheating time 60min, 1 to 3 steps cycled 2 times Vacuum drying: Step 4: vacuum (50-100) Pa; Step 5: vacuum drying 25min (50-100) Pa; Step 6: nitrogen drying 10min 80kPa; 4 to 6 cycles 8 times. Cooling: Cooling temperature: <50℃, drying air dew point: ≤-40℃. Baking temperature is 90±5℃, baking time is 6h, and contact baking method is adopted.

[0032] Primary injection parameters: injection room dew point ≤-40℃, (1) vacuum time ≤50s, negative pressure (-75±5) kPa, vacuum pressure holding time 30s; (2) step filling positive pressure: nitrogen filling 1s, pressure holding 20s; nitrogen filling 2s, pressure holding 20s, nitrogen filling 2s, pressure holding 30s, nitrogen filling 3s, pressure holding 30s, nitrogen filling 2s, pressure holding 30s, positive pressure ≥450kPa, then pressure holding; (3) positive pressure holding time ≥500s, pressure relief time 60s; (4) cycle 2 times. Then high temperature immersion for 24h.

[0033] Then, high-temperature forming is carried out at negative pressure of (-80 ±5) kPa, and the vacuum time is 2~3 minutes. The workshop temperature is controlled at (45±3)℃, and the dew point is ≤-40℃. The forming process steps are set as (1) standby for 1 minute; (2) 2500mA constant current charging, voltage limit 3.65V, time limit 25min; (3) standby for 1min (4) 10000mA constant current charging, voltage limit 3.65V, time limit 60min; (5) standby for 1min.

[0034] In step (4), the diaphragm is a PE ceramic diaphragm coated with PMMA large particle glue, the electrolyte is a special electrolyte for lithium iron, the solvent is a mixed solvent composed of EC, PC, and EMC, the lithium salt is LiPF6, and LIFSI is added to improve high temperature cycle, and the film-forming additive is VC; the mass ratio of EC, PC, EMC, VC, and LiPF6 is 31.2:4.0:49.5:2.5:12.8, and the conductivity is 12 mS / cm. The higher conductivity can Li + Migration speed in electrolyte, improving rate, VC as film-forming additive.

[0035] Control group 1: Preparation of positive electrode slurry: Figure 3 The process shown in the figure is prepared, and the materials LFP:SP:GO:PVDF= 96.8:0.5:0.7:2.0 and NMP1 are weighed according to the following mass percentages and put into the feeding mixer. According to the flow time, spiral mixing is carried out, and the main screw speed is (550±10) rpm and slowly stirred for half an hour, - the main screw solid content is (70%±2), the main screw discharge viscosity is 6000-10000, mPa·s, and then the high-speed disperser is used for large particle crushing, and then the high-speed dispersion axe is used for high-speed stirring for 4h, and the revolution and rotation are carried out as follows Figure 1 The data shown in the figure are used to measure the viscosity and solid content of the slurry. The solid content is controlled at 64%, and the viscosity range is (3000-8000) mPa·s. The moisture content in the workshop is strictly controlled to be less than 25% during the whole process to obtain the positive electrode slurry. Preparation of negative electrode slurry: Figure 2The process shown in the figure is prepared, except that the raw materials do not contain super conductive agent, and the negative electrode ratio is different, and the ingredients are prepared according to the following mass percentage, C: SP: SBR (solid content): CMC = 96.5: 0.5: 1.8: 1.2; then spiral mixing is carried out, and then scraping is carried out. The main screw speed is (550 ± 10) rpm and slowly stirred for half an hour. The main screw solid content is (70 ± 2), the main screw discharge viscosity is 6000-10000 mPa·s and the solid content is (52 ± 3)%. Then high-speed dispersion is carried out, the speed is (4200 ± 200) rpm, and the slurry viscosity and solid content are measured. The solid content is controlled at 64%, and the viscosity range is 3000-8000) mPa·s).

[0036] Pole sheet preparation: The prepared positive electrode slurry and negative electrode slurry are coated on the positive electrode collector and negative electrode collector respectively. The surface density of the positive and negative electrodes is single-sided: (182±2) g / m 2 , double-sided: (364±3) g / m 2 , negative electrode single side: (86±2) g / m2; double sides: (172±3) g / m 2 ; Rolling, the positive electrode rolling thickness is (174±2)μm, the negative electrode rolling thickness is (110±2)μm, and the positive and negative electrode slitting widths are 124 / 128mm; then, the steps (3), (4), and (5) are completed in the same manner as in Example (1) to prepare an iron-lithium square battery.

[0037] In step (4), the diaphragm is a PE ceramic diaphragm coated with PMMA large particle glue, the electrolyte is a special electrolyte for lithium iron, the solvent is a mixed solvent composed of EC, PC, and EMC, the lithium salt is LiPF6, and the film-forming additive is VC; the mass ratio of EC, PC, EMC, VC, and LiPF6 is 31.2:4.0:49.5:2.5:12.8, and the conductivity is 12 mS / cm. The higher the conductivity, the better the Li + Migration speed in electrolyte, improvement rate, VC as film-forming additive The batteries prepared in Example 1 and Control Group 1 were tested, and the results are shown in Table 1, wherein the battery capacity is in accordance with the national standard GBT31485. In a constant temperature chamber at 25°C, the battery monomer is discharged at 1C to 2.0V and then left to stand for 1h; charged at 1C constant current to 3.65V, and then stopped charging after constant voltage to 0.05C; discharged to a cut-off voltage of 2.0V, and the capacity was recorded, cycled 5 times, and then fully charged at 1C, and then discharged at 6.5C and 9.5C for 5min respectively, and the charge and discharge capacity during the process as well as the cut-off voltage and maximum temperature rise after 5 minutes were recorded. The specific results are shown in Figure 1.

[0038] Table 1

[0039] From Table 1 and Figure 3-4 It can be seen that the battery prepared in the embodiment meets the requirements of 6.5C and 9.5C discharge, and the capacity retention rates are 93.6% and 92.31% respectively. The maximum temperature of 6.5C discharge for 5 minutes is 36.04°C, and the maximum temperature rise of 9.5C discharge for 5 minutes is 47.6°C, which is less than 60°C. Moreover, compared with the control group, the 6.5C capacity retention rate is 14% higher, the 9.5C discharge capacity retention rate is increased by 22.68%, the 6.5C discharge temperature is reduced by 10°C, and the 9.5C discharge temperature is reduced by 22°C.

[0040] The discharge curves of the batteries prepared in Example 1 and the control group at different rates are as follows: Figure 7 As shown, from Figure 7 It can be seen that the prepared battery has good rate performance and small polarization.

[0041] Figure 5 and Figure 6 The figure is a cycle trend diagram of the batteries prepared in Example 1 and Control Group 1 at different temperatures.

[0042] Depend on Figure 5 and 6 It can be seen that the battery is first charged and discharged at 1C / C at room temperature 25°C for cycle testing. At 25°C, the embodiment has a cycle of 3140 weeks with a retention rate of 87.53%, while the control group has a cycle of 2999 weeks with a retention rate of 82%. The battery is charged and discharged at 1C / C at the same high temperature of 45°C for cycle testing. At 45°C, the embodiment has a cycle of 2642 weeks with a retention rate of 82.30%, while the control group has a cycle of 1754 weeks with a capacity retention of 81%. The room temperature cycle is improved by 30%, and the high temperature cycle is improved by 50%. In the case of high-rate discharge, the 1C / 6.5C discharge cycle is significantly improved compared with the control group, which can be increased from 600 weeks to 2000 weeks, an increase of 300%.

Claims

1. A negative electrode slurry, characterized in that: It includes the following components by mass: Negative electrode active material 90~94.8 parts; 1.9~2.2 parts of negative electrode conductive agent; Super conductive agent 0.01~0.05 parts; 1.2-1.4 parts of carboxymethyl cellulose; 2 parts of negative electrode binder; Wherein, the super conductive agent is carbon nanotube slurry.

2. The negative electrode slurry according to claim 1, characterized in that The negative electrode binder is styrene-butadiene rubber modified by acrylic acid.

3. The negative electrode slurry according to claim 1 or 2, characterized in that: The negative electrode active material is graphite; The graphite raw material has an inlay structure ratio of 20-40%; the graphite is a secondary particle structure, the aggregate particle size D50 is 6-8 μm, and the secondary particle D50 is 11 μm-14 μm.

4. The negative electrode slurry according to claim 1 or 2, characterized in that: The average tube diameter of the super conductive agent is 1.56-1.8 nanometers, the slurry aspect ratio is 1340-2340, and the resistance conductivity is 0.28-0.34 Ocm.

5. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm, an electrolyte, and shell-related structural parts and a connecting sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and the negative electrode slurry according to any one of claims 1 to 4 coated on the negative electrode current collector.

6. The lithium-ion battery according to claim 5, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on the surface of the positive electrode current collector; The positive electrode slurry comprises the following components in parts by weight: 90-95.5 parts of positive electrode active material; 1.3-1.8 parts of positive electrode conductive agent; 1.8-2.2 parts of positive electrode conductive slurry; and 2.0 parts of positive electrode binder.

7. The lithium-ion battery according to claim 6, characterized in that: The positive electrode active material is lithium iron phosphate, with a gram capacity of ≧145 mAh / g, and a median particle size D 50 0.6~1.5um, ultimate compaction density 2.25~2.3g / cm 3 ; The positive electrode conductive agent is a mixture of graphene and conductive carbon black; The positive electrode binder is polyvinylidene fluoride, and the main chain of polyvinylidene fluoride is -(CH2-CF2) n -chain segment, and at the same time, molecules containing -COOH functional groups are embedded in the main chain segment.

8. The lithium ion battery according to claim 5 or 6, characterized in that: The diaphragm is a PE ceramic diaphragm or a PP base film, and at the same time, the PE ceramic diaphragm is coated with PMMA large particle glue; The conductivity of the electrolyte is 10~12 mS / cm, and the electrolyte is prepared by dissolving lithium salt in an organic solvent and adding additives; wherein the organic solvent is a mixed solvent composed of EC, PC, and EMC; the lithium salt is at least one of LiClO4, LiPF6, LiAsF6, LiBF4, Li(CF3SO3) and Li(CF3SO2)2N; the additive is at least one of sulfur-containing organic matter, fluorinated organic matter, vinylidene-containing organic matter, nitriles, boric acid and silicates.

9. The lithium ion battery according to claim 5 or 6, characterized in that: The single-sided surface density of the positive electrode sheet is 125-150 g / m, and the average compaction density is 2.13-2.18; The surface density of the negative electrode sheet is 60-70 g / m, and the average compaction density is 1.35-1.

45.

10. The method for preparing a lithium ion battery according to any one of claims 5 to 9, comprising the following steps: S1. Prepare positive electrode slurry by mixing the raw materials of positive electrode slurry according to the main screw slurry method; S2, preparing negative electrode slurry by mixing raw materials of negative electrode slurry according to the main screw slurry method; S3, coating the positive electrode slurry and the negative electrode slurry on the positive electrode collector and the negative electrode collector respectively, and baking to obtain the positive electrode sheet and the negative electrode sheet; S4, rolling, slitting, winding, assembling, shelling, baking, liquid injection, sealing, infiltration, formation, aging, and capacity separation are performed on the positive electrode sheet and the negative electrode sheet respectively to obtain the lithium ion battery.

Citation Information

Patent Citations

  • Preparation method for artificial graphite negative electrode material for lithium ion battery

    CN105958070A

  • Ternary lithium ion battery

    CN108493442A

  • Negative electrode slurry, lithium ion battery containing the same and preparation method thereof

    CN111653784A